Hubungan Aktivitas Bermain Kelompok dengan Kemampuan Kolaborasi Anak Usia Dini - Meutya Amalia Pikoli; Melisa Daud; Alya Airmas; Siti Fadila; Siti Fardianti Suli; Mita Sari (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to determine the relationship between group play activities and children's cooperation skills in early childhood education settings. This study uses a quantitative approach with a correlational design. Group play activities are considered important in developing social-emotional aspects, especially children's ability to cooperate, communicate, and interact positively with peers. Cooperation skills in early childhood include the ability to share tasks, help friends, follow rules, and achieve common goals during learning and play activities. Data collection techniques were carried out through observation and questionnaires using a Likert scale. The results of previous studies indicate that group play activities contribute positively to the development of children's cooperation skills because children are trained to interact, solve problems together, and build social relationships. Therefore, teachers and parents are expected to provide more opportunities for children to participate in group play activities that are educative and interactive..